2022
DOI: 10.1002/pan3.10387
|View full text |Cite
|
Sign up to set email alerts
|

Communicating nature during lockdown – How conservation and outdoor organisations use social media to facilitate local nature experiences

Abstract: nature during lockdown -how conservation and outdoor organisations use social media to facilitate local nature experiences', People and Nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…"I think it is that it is a way of passing on information in an educational way, so indirectly, the information also has to get into the minds of people who go through our social media." -PI4 These findings align with the recent studies that demonstrated a positive impact of social media on social media users' environmental awareness and PEBs (Arts et al, 2022;Mallick & Bajpai, 2019;Shah et al, 2021;Xie & Madni, 2023).…”
Section: "But We Still Have Relatively Frequent Exchanges With People...supporting
confidence: 85%
See 1 more Smart Citation
“…"I think it is that it is a way of passing on information in an educational way, so indirectly, the information also has to get into the minds of people who go through our social media." -PI4 These findings align with the recent studies that demonstrated a positive impact of social media on social media users' environmental awareness and PEBs (Arts et al, 2022;Mallick & Bajpai, 2019;Shah et al, 2021;Xie & Madni, 2023).…”
Section: "But We Still Have Relatively Frequent Exchanges With People...supporting
confidence: 85%
“…Arts et al' (2022) study showing that NGOs used social media during the COVID-19 lockdowns to connect people and create an online conservation community. Finally, the COVID-19 lockdowns drove PNAs to engage with the experiential function of their social media as they increased their use of images and pictures to counter the lack of exposure to Nature experienced by the French population.…”
mentioning
confidence: 99%
“…Other publications complement this analysis by focusing on the content of the message, which can examine the appearance of certain keywords [45] or the feelings and emotions evoked in the tweets [46]. Besides the studies purely based on sentiment analysis [29], other works focus on the network generated by the messages [31], on their popularity, or on the engagement they foster [47]. This article grounds the exploration of urban forestry as more-than-human practice through the examination of the contents posted on the official Twitter account of Tokyo's Rinshinomori Park: @ParksRinsi.…”
Section: Methodsmentioning
confidence: 99%
“…To process an enormous amount of data, scholars frequently apply filters according to geolocation or specific content in the messages. To a lesser extent, there are fewer studies that use a single Twitter thread [48], or the content generated by a reduced number of specialized accounts [47]. Building along this line, the present study is the first that relies on the detailed analysis of the content generated by a single account, contributing with a novel approach to the existing body of research.…”
Section: Twitter As a Research Toolmentioning
confidence: 96%
“…The purpose of media is to facilitate communication (Arts et al, 2022;Ansari & Khan, 2020;Chatterjee & Kar, 2020& Mheidly & Fares, 2020. But media can provide students with a visual experience during learning, simplify complex concepts, and embody abstractions.…”
Section: Introductionmentioning
confidence: 99%